Counter-imagination as interpretive practice: futuristic fantasy and The Fifth Element - Aoki, Eric, author; Ott, Brian L., author; Organization for Research on Women and Communication, publisher (Colorado State University. Libraries, 2004)
This essay concerns the relationship between popular cinematic visions of the future and present day identity politics. The authors argue that despite its futuristic setting celebrating technological progress and multiculturalism, Luc Besson's 1997 film The Fifth Element constructs sexual and racial difference in a manner that privileges and naturalizes White heterosexual masculinity. The essay offers counter-imagination as an interpretive practice that destabilizes the categories of sexual and racial difference as they are negotiated within appeals to popular imagination.
Brian Ott was a professor in the Department of Speech Communication at Colorado State University.
Keywords: science fiction films; The Fifth Element; counter-imagination; sex; race